Clinical evaluation of safety and complications of the nasal tip defatting in rhinoplasty - Niazi, Feizollah; Niazi, Sana; Alizadeh Otaghvar, Hamidreza; Goravanchi, Farhood (Researcher Bulletin of Medical Sciences, 2019)
Objective: Nasal tip refinement is an important objective in aesthetic rhinoplasty and one of the surgical options for soft tissue management in very thick bulbous skin and subcutaneous noses is tip defatting. The aim of this study was to evaluate the safety and complications of tip defatting in thick skin and bulbous noses. Methods: Among 527 patients that underwent rhinoplasty in Modaress hospital between February 2011 and January 2014, nasal tip defatting were performed in 162 of these patients. Intraoperatively and in follow up examinations, any signs of skin congestion, ischemia, hematoma, and skin quality evaluated. Results: Among 162 patients who had performed tip defatting [39 (24.1%) male patients and 123 (75.9%) female], complications were skin congestion in 6 patients (3.7%), ecchymosis in 10 patient (6.1%). There were no cases of skin necrosis, skin perforations or skin irregularity. Conclusion: Our study and many previous studies show that tip defatting in association with lower lateral cartilage reduction is a safe and helpful method in correction of bulbous nose deformity